Radial rasis function for non-matching mesh interpolation in parallel solving FSI problem. (28th March 2019) - Kopysov, Sergey; Kuzmin, Igor; Novikov, Alexander; Nedozhogin, Nikita; Tonkov, Leonid
In strongly coupled fluid-structure interaction simulations, the fluid dynamics and solid dynamics problems are solved independently on their own meshes. Therefore, it becomes necessary to interpolate the physical properties (pressure, displacement) across two meshes. In the present paper, we propose to accelerate the interpolation process by the method of radial basis functions using the matrix-free solution of the system of equations on a GPU. Also, we reduce the number of equations in the system by using an adaptive algorithm for choosing interpolation points.